Key business characteristics of Chinese entrepreneurs in the Malaysian furniture industry - Tey, Wee Chong (2018)
The rapid growth of the Malaysian furniture industry over the last two decades had successfully transformed an inferior cottage-based industry into a multi-billion Ringgit industry. The Malaysian furniture industry is predominated by small and medium enterprises (SMEs) and of Chinese entrepreneurs. Thus, this research was conducted to study the key business characteristics of Chinese entrepreneurs, which enabled them to sustain and dominate in the Malaysian furniture industry. Results from this research showed that the majority of the respondents practiced family management system and obtained the start up capital through bank loans. Other key characteristics found included respondents were focused on the export market, manufactured products based on their original design and the employment rate of foreign-contract workers was higher compared to local workers. The results concluded that Chinese entrepreneurs were more focused on business aspects, such as market, management and financial in their furniture businesses.